ASSOCIATION OF SOCIAL FRAILTY WITH PHYSICAL FUNCTION AND NEUROPSYCHOLOGICAL STATUS AMONG OLDER ADULTS. (11th November 2018) - MA, L; Tang, Z; Sun, F; Li, Y; Chan, P
Abstract: Frailty is associated with increased risks of disability and mortality. The social and psychological domains of frailty are often neglected, despite social relationships and support being viewed as determinants thereof. Social factors, which play a role in modulating the adverse health-related outcomes of frailty, are integral to the health of older adults. However, research into the relationship between social frailty (SF), physical function, cognition and depression remains limited. We aimed to investigate the association of SF with physical function and neuropsychological status in a Chinese older population. 1697 community-dwelling older adults from the Beijing Longitudinal Study of Aging (BLSA) with an 8-year follow-up were included. SF was assessed by the HALFT scale with 5 items (inability to help others, limited social participation, loneliness, financial difficulty, and not having anyone to talk to). Balance test, chair-stand test, ADL and IADL were also assessed. Physical activity and frailty were measured by BLSA-PAQ and frailty index, respectively. Cognition was measured using the mini-mental state examination and the Center for Epidemiologic Studies Depression Scale was used to assess depression. The results showed that SF, as defined by the HALFT scale, was associated with worse physical function, cognitive impairment, and depression. The Cox proportional hazards analysis showed SF and pre-SF predicted 8-year mortality (HR 3.5–6.1 and 1.9–2.9, respectively). This study revealed that SF was associated with both physical function and neuropsychological status, which indicates that SF should be assessed and taken into account in the implementation of multifaceted prevention strategies for older adults.